A painful monument: The failure monument for francoist violence victims in Madrid (2004-2020) - Garbero, Vanesa; Palacios González, Daniel (Hispania Nova, 2021)
This article analyses processes of social, political and cultural struggle for the construction of a monument in memory of people executed by the Franco regime in Madrid (mostly next to the Almudena cemetery) in the post-war period and the resignification by the new municipal government during its construction. It also examines memories and social meanings of historical political repression under debate during the attempts for carrying out such project by different actors. The research work shows that the city of Madrid remains a hostile territory to state-legitimised public markings that give visibility and recognition to the victims of the Spanish military dictatorship.